The bittersweet economics of different cacao production systems in Colombia, Ecuador and Peru - Charry, Andres; Perea, Carolay; Ramírez, Karen; Zambrano, Guillermo; Yovera, Fredy; Santos, Adriana; Jimenez, Tito; Romero, Miguel; Lundy, Mark; Quintero, Marcela; Pulleman, Mirjam (Elsevier, 2025)
Cacao production takes place in diverse environments and agricultural systems, with its performance and income generation potential depending on multiple contextual factors. The crop has been promoted among smallholders in South America as a driver for sustainable rural development, but a systematic comparison of the economic performance of diverse cacao production systems in this region was missing, which led to a lack of consistency and clarity on the conditions that enable the crops' success in terms of profitability and income generation for farmers.